A Concise and Efficient Approach to 2,6-Disubstituted 4-Fluoropyrimidines from α-CF3 Aryl Ketones - Liu, Fangran; Zhang, Xiaofei; Qian, Qun; Yang, Chunhao (Synthesis, 2020)
Herein, a concise and efficient protocol to synthesize a series of 2,6-disubstituted 4-fluoropyrimidines as universal and useful building blocks in medicinal chemistry is reported. From readily accessible α-CF3 aryl ketones and different amidine hydrochlorides, this method provides a very practical approach to this kind of compounds under mild conditions with good to excellent yields.
Keywords: fluoropyrimidine; α-CF3 aryl ketone; metal-free; mild conditions